Persuasive technology for enhanced learning behavior in higher education - Yohana Dewi Lulu Widyasari; Lukito Edi Nugroho; Adhistya Erna Permanasari (International Journal of Educational Technology in Higher Education, 2019)
Abstract Obtaining quality learning behavior requires constant improvement. The development of learning methods often unsupported changes in the behavior of participants. This condition causes reluctance to use new learning methods by some users. Meanwhile, technological developments, especially Web 2.0, have the ability to change the way people communicate and interact. This study used the features and capabilities of Web 2.0 to improve learning behavior. The use of this technology will be adjusted with learning methods, especially online-learning that overgrows nowadays. The concept of an integrated system applied a persuasive strategy to bring persuasion. Modifications e-learning were done by combining the concepts of Web 2.0 and persuasive system. Tests were performed on aspects that affect the user’s intentions by comparing the initial and final conditions after the intervention. The behavior changes were expected to improve user involvement and intention in online learning. The results show that the modified technology by using persuasive concept can improve the users’ intention.